Journeys that opened up the world : women, student Christian movements, and social justice, 1955-1975 - Evans, Sara M. (Sara Margaret), 1943- (Rutgers University Press, 2003)
"This volume is a collection of inspiring memoirs from sixteen women active in the civil rights movement, anti-war campaigns, and the rise of feminism in the Cold War era. It places religious activism at the center of social movements previously thought of as largely secular." "The book reads as a riveting collection of dramatic personal stories of small-town girls thrust into leadership during watershed events of modern American history. The SCM introduced young women to activism in other parts of the country and around the world. As leaders, thinkers, and organizers, they encountered the social realities of poverty and racial prejudice and worked to combat them. The SCM took women to Selma and Montgomery, to Africa and Latin America, and to a lifelong commitment to work for social justice."--Jacket